Estudio para la implementación de un sistema informático para el registro de citas médicas por internet del Centro de Atención Carlos Luis Morales Reina de la ciudad de Babahoyo - Cabrera Gaibor, Rosalia Sasha (2020)
This case study performs an analysis and appreciation of the development of a web page for the Carlos Luis Morales Reina care and comprehensive training center in the city of Babahoyo, where new patients and employees of the institution will be scheduled with availability of schedules. emphasis on the strategy to successfully promote the website. With the scheduling of medical appointments of this system we can achieve that there is a control for the information and that when verifying a patient can modify their information, with this we can achieve an application that allows time to perform other activities such as the shift and verification process of medical data. Carlos Pesadores doctor in general medicine from the center of attention and training in integral health of the rivers, results of the survey carried out to people of Babahoyo, and of the bibliographic material that supports this case study. The web system of the Carlos Luis Morales Reina care center complies with the assigned investigation processes in each role, at the time that patients require information, only the administrator is in charge of the modification. In conclusion, analyzing the technical, operational and economic feasibility, it was established that the implementation of the website of the comprehensive care and training center is feasible, since it does not require investment and the institution has the technological equipment and software for a creation and implementation.